PPVED: A machine learning tool for predicting the effect of single amino acid substitution on protein function in plants. Issue 7 (27th April 2022) - Gou, Xiangjian; Feng, Xuanjun; Shi, Haoran; Guo, Tingting; Xie, Rongqian; Liu, Yaxi; Wang, Qi; Li, Hongxiang; Yang, Banglie; Chen, Lixue; Lu, Yanli
Summary: Single amino acid substitution (SAAS) produces the most common variant of protein function change under physiological conditions. As the number of SAAS events in plants has increased exponentially, an effective prediction tool is required to help identify and distinguish functional SAASs from the whole genome as either potentially causal traits or as variants. Here, we constructed a plant SAAS database that stores 12 865 SAASs in 6172 proteins and developed a tool called Plant Protein Variation Effect Detector (PPVED) that predicts the effect of SAASs on protein function in plants. PPVED achieved an 87% predictive accuracy when applied to plant SAASs, an accuracy that was much higher than those from six human database software: SIFT, PROVEAN, PANTHER‐PSEP, PhD‐SNP, PolyPhen‐2, and MutPred2. The predictive effect of six SAASs from three proteins in Arabidopsis and maize was validated with wet lab experiments, of which five substitution sites were accurately predicted. PPVED could facilitate the identification and characterization of genetic variants that explain observed phenotype variations in plants, contributing to solutions for challenges in functional genomics and systems biology. PPVED can be accessed under a CC‐BY (4.0) license via http://www.ppved.org.cn .